Effective distribution of gold nanorods in ordered thick mesoporous silica: a choice of noninvasive theranostics - Prasad, Rajendra; Selvaraj, Kaliaperumal (ACS Applied Materials & Interfaces, 2023)
Porous silica coated gold nanorod core-shell structures demonstrate a multifunctional role in bioimaging, drug delivery, and cancer therapeutics applications. Here, we address a new approach for effective distribution of gold nanorods (GNRs) in a mesoporous silica (MS) shell, viz., one nanorod in one silica particle (GMS). We have studied that silica coating presents major advantages for the better biocompatibility and stability of GNRs. In this study, two different thicknesses of silica shell over GNRs have been discussed as per the application's need; GNRs in thin silica (11 nm) are fit for phototherapy and bioimaging, whereas thick and porous silica (51 nm) coated gold nanorods are suitable for triggered drug delivery and theranostics. However, effective distribution of GNRs in ordered architecture of thick mesoporous silica (MS, more than 50 nm thickness) with high surface area (more than 1000 m(2)/g) is not well understood so far. Here, we present methodical investigations for uniform and highly ordered mesoporous silica coating over GNRs with tunable thickness (6 to 51 nm). Judicious identification and optimization of different reaction parameters like concentrations of silica precursor (TEOS, 1.85-43.9 mM), template (CTAB, 0.9-5.7 mM), effect of temperature, pH (8.6-10.8), stirring speed (100-400 rpm), and, most importantly, the mode of addition of TEOS with GNRs have been discussed. Studies with thick, porous silica coated GNRs simplify the highest ever reported surface area (1100 m(2)/g) and cargo capacity (57%) with better product yield (g/batch). First and foremost, we report a highly scalable (more than 500 mL) and rapid direct deposition of an ordered MS shell around GNRs. These engineered core-shell nanoparticles demonstrate X-ray contrast property, synergistic photothermal-chemotherapeutics, and imaging of tumor cell (96% cell death) due to released fluorescent anticancer drug molecules and photothermal effect (52 degree celsius) of embedded GNRs. A deeper insight into their influence on the architectural features and superior theranostics performances has been illustrated in detail. Hence, these findings indicate the potential impact of individual GMS for image guided combination therapeutics of cancer.
Keywords: CombinationTherapy; Contrast Agent; Core-ShellStructure; GoldNanorods; Imaging; Mesoporous silica; Nanoparticles; TheranosticsIntervention

Hydrogel electrolyte-mediated in situ Zn-anode modification and the Ru-RuO2/NGr-coated cathode for high-performance solid-state rechargeable Zn-air batteries - Kharabe, Geeta Pandurang; Verma, Tushar; Barik, Sidharth; Urkude, Rajashri R.; Ayasha, Nadeema; Ghosh, Biplab; Krishnamurty, Sailaja; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2025)
This work aims to deal with the challenges associated with designing complementary bifunctional electrocatalysts and a separator/membrane that enables rechargeable zinc-air batteries (RZABs) with nearly solid-state operability. This solid-state RZAB was accomplished by integrating a bifunctional electrocatalyst based on Ru-RuO2 interface nanoparticles supported on nitrogen-doped (N-doped) graphene (Ru-RuO2/NGr) and a dual-doped poly(acrylic acid) hydrogel (d-PAA) electrolyte soaked in KOH with sodium stannate additive. The catalyst shows enhanced activity and stability toward the two oxygen reactions, i.e., oxygen reduction and evolution reactions (ORR and OER), with a very low potential difference (Delta E) of 0.64 V. The computational insights bring out the electronic factors contributing to the enhanced catalytic activity of Ru-RuO2/NGr based on the charge density difference (CDD) between the interfaces. The disadvantages of the existing solid-state RZABs, such as their limited lifespan brought on by passivation, dendritic growth, corrosion, and shape change, have also been taken into account. The introduction of the stannate additive to the electrolyte induced an in situ Zn-anode modification, which subsequently improved the interfacial stability of the ZABs and, hence, the battery life cycles. The experimental observations reveal that, during the charging process, the Sn nanoparticles enable the homogeneous Zn deposition on the surface of the anode. Thus, the in situ Zn-anode surface modification assisted in achieving a high-rate cycle capability, viz., the homemade catalyst-based system exhibited continuous charge-discharge cycles for 20 h at a current density of 2.0 mA cm-2, with each cycle lasting for 5 min.
Keywords: Bifunctional Electrocatalyst; Core-ShellStructure; DFT study; electrolyte additive; Hydrogel; solid-state rechargeable zinc-airbattery; X-ray absorption spectroscopy